Service Reliability Test Method for Anticorrosion Coatings on the Compressor Outlet Pipelines of Natural Gas Stations - Nie, Hailiang; Ma, Weifeng; Deng, Kang; Zhao, Guangqiang; Mao, Ying; Ren, Junjie; Dang, Wei; Wang, Ke; Cao, Jun; Yao, Tian; Liang, Xiaobin (ACS omega, 2023)
Compressor outlets are subject to high temperatures and vibrations; when pipelines are subject to such conditions, degradation of the anticorrosive layer on the pipeline is likely. Fusion-bonded epoxy (FBE) powder coating is the most common type of anticorrosion coatings on compressor outlet pipelines. It is necessary to study the reliability of anticorrosive layers in compressor outlet pipelines. In this paper, a service reliability test method for the corrosion-resistant coatings of compressor outlet pipelines of natural gas stations is proposed. Testing involving the simultaneous exposure of the pipeline to high temperatures and vibrations is conducted to evaluate, on a compressed timescale, the applicability and service reliability of FBE coatings. The failure mechanism of FBE coatings exposed to high temperatures and vibrations is analyzed. It is found that, due to the influence of initial imperfections in the coatings, FBE anticorrosion coatings typically do not meet the standard requirements for use in compressor outlet pipelines. After simultaneous exposure to high temperatures and vibrations, the impact resistance, abrasion resistance, and bending resistance of the coatings are found not to meet the requirements for their intended applications. It is therefore suggested that FBE anticorrosion coatings be used with extreme caution in compressor outlet pipelines.